La formation continue des enseignants au Niger: vers une amélioration de leurs pratiques de classe - Nassirou, Mamane (Status Quaestionis, 2022)
This research work attempts to highlight the eminently important role of the in-service training of French teachers in their classroom practices, in particular by the added value it brings in their development. Using data from field surveys, the study tries to highlight the benefit that novice and non-novice teachers can derive from this retraining activity of in-service training. This research is therefore an invitation to the educational authorities of Niger, in order to provide its education system with professionally qualified teachers.